Beginning JavaScript : the ultimate guide to modern JavaScript development - Ferguson, Russ (Apress, 2019)
Discover everything you need to know to get up-to-speed with JavaScript development and add dynamic enhancements to web pages. This completely updated third edition reveals how the code works and when to use closures, constants, and execution content. Starting with the basics, you'll see how to employ prototypical inheritance, as well as memory management, variable hoisting and event bubbling. Also covered is an introduction to Node.js and package managers, key to understanding the tools necessary in front-end development and how they are used with current JavaScript frameworks. JavaScript is one of the most important technologies on the web, providing the means to add dynamic functionality to your web pages and serving as the backbone of working with frameworks like Angular and React. Beginning JavaScript, Third Edition will take you from being a JavaScript novice to working freely with this important technology - begin your JavaScript journey today!